Public confidence in police competency to combat crime / Gopala Krishnan Sekharan Nair … [et al.] - Sekharan Nair, Gopala Krishnan; Luqman, Azyanee; Shanmuggam, Saravanan; Vadeveloo, Thenmolli (Faculty of Administrative Science and Policy Studies, 2012)
In recent times, the Malaysian public has expressed fears of increasing crime rate. However, the authorities have tried to dispel public fears by stating that crime rate has actually taken a dip and public worry is more a matter of perception rather than a fear caused by a real and genuine basis. The police point out that there will be a time gap between reduction of crime rate and a raise in public confidence as public confidence does not go up immediately when there has been an improvement in the crime situation. This paper investigated the level of fear of the public pertaining to being a victim of crime. Additionally, this paper investigated the factors that influenced the public opinion of the police such as police effectiveness in combating crime, corruption, brutality and personal links between police and the public. It is essential that the public should have a positive perception of the police force so that the force may be able to count on public cooperation in their efforts to combat crime and maintain public order. A sample size of 407 was taken for this study. The sample was stratified according to age groups and the level of education. It was found that most of the educated members from urban areas were not happy with the police as they felt that the police could be more effective in combating crime. This group also registered a higher fear level of being a crime victim. Fear of becoming a crime victim amongst the respondents. The respondents also felt that the recently repealed Emergency Ordinance (EO) which enables detention without trial should be reinstated. The public also felt that the police need more formidable intelligence gathering and the courts should mete out heavier punishment.